2017
DOI: 10.1177/1479164117744490
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of barriers to entry of cardiac rehabilitation in patients with diabetes: Using data from the National Audit of Cardiac Rehabilitation

Abstract: This study confirms, in a new UK population with over 121,002 eligible patients, that there is a statistically significant drop in patients with diabetes taking up cardiac rehabilitation. This study is unique in looking at all four key diagnosis and treatment groups and comparing them to those taking up cardiac rehabilitation. To achieve the target of 65% uptake set by NHS England, improvements in identifying and targeting complex patients, such as those with diabetes, need to be adopted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…Reported attendance rates in Australia vary considerably but range from 20% to 40% (Clark et al, ; Jelinek, Thompson, Ski, Bunker, & Vale, ; Redfern, Ellis, Briffa, & Freedman, ; Wachtel, ), while completion rates range from 31% to 56% (Tavella et al, ; SA Minimum database 2017). These figures are similar to those reported in the UK (Harrison, Doherty, & Phillips, ) and the US (Pack et al, ). One of the commonly cited barriers to CR attendance and completion is poor referral (National Heart Foundation NHF, ).…”
Section: Introductionsupporting
confidence: 90%
“…Reported attendance rates in Australia vary considerably but range from 20% to 40% (Clark et al, ; Jelinek, Thompson, Ski, Bunker, & Vale, ; Redfern, Ellis, Briffa, & Freedman, ; Wachtel, ), while completion rates range from 31% to 56% (Tavella et al, ; SA Minimum database 2017). These figures are similar to those reported in the UK (Harrison, Doherty, & Phillips, ) and the US (Pack et al, ). One of the commonly cited barriers to CR attendance and completion is poor referral (National Heart Foundation NHF, ).…”
Section: Introductionsupporting
confidence: 90%
“…571 However, several studies have also indicated that cardiac rehabilitation uptake is low in patients with DM. 571,572 Patient-centred care in DM…”
Section: General Aspectsmentioning
confidence: 99%
“…This guidance statement is aimed at helping front-line practitioners better manage the growing number of cardiac rehabilitation participants who have diabetes. (1) It has been developed and written by a group of practitioner-academics with a special interest in how diabetes management interacts with their practices in cardiology (3 authors), dietetics (1 author), rehabilitation therapy (1 author) or exercise science applied to metabolic care (2 authors). All of the authors have previous experience in contributing to national and international practice guidelines/standards in either cardiac rehabilitation and/or diabetes.…”
Section: Introduction and Aimsmentioning
confidence: 99%